Extended N-Arylsulfonylindoles as 5-HT6 Receptor Antagonists: Design, Synthesis & Biological Evaluation - Gonzalo Vera; Carlos F. Lagos; Sebastián Almendras; Dan Hebel; Francisco Flores; Gissella Valle-Corvalán; C. David Pessoa-Mahana; Jaime Mella-Raipán; Rodrigo Montecinos; Gonzalo Recabarren-Gajardo (Molecules, 2016)
Based on a known pharmacophore model for 5-HT6 receptor antagonists, a series of novel extended derivatives of the N-arylsulfonyindole scaffold were designed and identified as a new class of 5-HT6 receptor modulators. Eight of the compounds exhibited moderate to high binding affinities and displayed antagonist profile in 5-HT6 receptor functional assays. Compounds 2-(4-(2-methoxyphenyl)piperazin-1-yl)-1-(1-tosyl-1H-indol-3-yl)ethanol (4b), 1-(1-(4-iodophenylsulfonyl)-1H-indol-3-yl)-2-(4-(2-methoxyphenyl)piperazin-1-yl)ethanol (4g) and 2-(4-(2-methoxyphenyl)piperazin-1-yl)-1-(1-(naphthalen-1-ylsulfonyl)-1H-indol-3-yl)ethanol (4j) showed the best binding affinity (4b pKi = 7.87; 4g pKi = 7.73; 4j pKi = 7.83). Additionally, compound 4j was identified as a highly potent antagonist (IC50 = 32 nM) in calcium mobilisation functional assay.